Personal Development for Life and Work - Masters, L. Ann and Wallace, Harold R., 1929- (Andover, Melbourne Cengage Learning, 2011)
Helps students recognize the importance of soft skills, critical thinking skills, and work ethics in the workplace. This title includes self-assessments, case studies, and activities that are suitable for both business and personal situations
Include Index
Keywords: Personality and occupation -- Success -- Vocational guidance